Success and failure of English as a foreign language lecturer in applying the assessment as learning in higher education - Toto Hermawan; Agung Prihantoro (Ömer Gökhan Ulum, 2021)
The paper intends to describe how English as a Foreign Language lecturers succeed and fail to apply the assessment as learning in teaching and learning programs in higher education. The explanatory mixed-methods were conducted to survey 57 respondents in the higher institutions in the Special Province of Yogyakarta, Indonesia and to interview 8 respondents in the high-level group of applying the assessment. Two criteria of the success and failure are (1) to promote active and proactive learning and (2) to result in good learning outcome. The findings indicate that some of the lecturers succeeded to promote active and proactive learning of peer assessment, self-assessment, self-reflection in and outside classrooms and no criteria compliance, to provide oral and written feedback to students, and to result in good final grade. A lecturer failed to apply the assessment for her limited knowledge and some lecturers failed because of their low achieving students and of having no time to give feedback.